The origins and maintenance of species boundaries in Jamesbrittenia O. Kuntze (Scrophulariaceae: Manuleae) - Moncrieff, Glenn (Department of Biological Sciences, 2017)
The genus Jamesbrittenia contains 83 species distributed throughout southern Africa. Many species produce attractive flowers and consequently their horticultural potential is currently being explored. Speciation patterns and reproductive isolation were investigated in order to identify trends that may apply at broader scales. Bayesian phylogenetic analysis was performed using plastid (rps 16 and psbA-trnH) and nuclear (GScp) sequence data. Relative divergence times were calculated using a relaxed clock method. Prezygotic isolation, measured as seed set resulting from interspecific crosses, correlated with divergence time. However, recently diverged, highly sympatric taxa deviated from the overall trend. This provides circumstantial evidence for reinforcement of reproductive barriers. Floral dissimilarity and divergence time were found to be useful in predicting hybridization reported in the wild (p<0.0001). Species pairs susceptible to hybridization were identified on the basis of their floral dissimilarity and divergence time in order to prevent potentially hybridizing species from being brought into contact. The inability to detect the dominant mode of speciation confounded interpretation of the results, as it was not possible to determine if the influence of geographic patterns on the evolution of reproductive isolation was a result of the mode of speciation or post-speciation evolutionary changes.